Fall 1985 report - Petersen, Peter C.et al (1985)
An annotated list of birds sighted by Peter Petersen and others. Includes a letter from Pete Petersen to Thomas Kent regarding photos of a Sage Thrasher dated December 1, 1985. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of Fall 1985. Epson - sheet feed/flatbed